Analisis Produk Unggul Daerah Berdasarkan Unggulan Komoditi Perkebunan pada Dinas Perkebunan dan Peternakan Kabupaten Pelalawan - Nasruddin, Nasruddin (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2024)
This research aims to identify regional superior products in Pelalawan Regency based on the potential of plantation commodities owned. The research method used is qualitative descriptive analysis with data collection through literature studies, in-depth interviews with the Pelalawan Regency Plantation and Livestock Office, institutions and plantation farmers. This research contributes to the development of the plantation sector in Pelalawan Regency by identifying regional superior products based on the potential of existing plantation commodities. Through qualitative descriptive analysis, this study concludes that the plantation sector commodity that is the advantage of the Pelalawan Regency region is oil palm commodity. The results of this research are expected to be a reference for local governments in formulating strategies for the development of the plantation sector, especially sustainable palm oil, a direction in the development of commodity potential plantation commodities as superior regional products so that they can improve the welfare of the community and the regional economy.